Occult hepatitis B virus infection in Moroccan HIV infected patients - Bajjou, Tahar; Elannaz, Hicham; Tagajdid, Mohamed Rida; Elghafouli, Hicham; Laraqui, Abdelilah; Abi, Rachid; Elhilali, Farida; Zouhdi, Mimoune; Lahlou, Idriss; Sekhsoukh, Yassine; Mrani, Saad (International Journal of Research in Medical Sciences, 2017)
Background: The purpose of this study is to assess the prevalence of Occult hepatitis B virus Infection (OBI) among antiretroviral treatment naïve HIV-1 infected individuals in Morocco and to determine factors favouring its occurrence. Methods: The retrospective study was conducted in the Mohammed V military teaching hospital in Rabat between January 2010 and June 2011. It included patients with confirmed HIV infection, tested negative to serological detection of HBV surface antigen (HBsAg) and did not received antiviral treatment or hepatitis B vaccine. All samples were tested for anti-HBc, anti-HBs and anti-HCV antibodies using enzyme immunoassay (ELISA). The detection of HBV DNA was performed by real-time PCR using two specific primers for a gene in the region C of the viral genome. The sensitivity of the technique was 20 copies/ml. Results: A total of 82 samples were analyzed, 19 (23 %) were found to have isolated anti-HBc, 07 (8.5%) with associated anti-HBc and Anti-HBs. No anti-HCV marker was detected on these screening samples. The HBV DNA was detected in 48 (58%) samples, of which, males constituted 58% (28/48). The mean age of these patients was 38 ± 8.2 (29-56), the median HIV-1 viral load and CD4 cell count HIV-1 infected patients were 127500 (54108-325325) copies/ml and 243 [80-385] cells/mm3 respectively and 27.1% (13/48) of these patients were found to have isolated anti-HBc. A significant correlations between DNA HBV and HIV viral load higher than 100000 copies/ml (P = 0.004), CD4 cell count lower than 400 cells/mm3 (P = 0.013, P = 0.006) and isolated anti-HBc samples (P <0.005) were founded. However there was no significant association with age, sex, transmission mode and clinical stage. Conclusion: The consequences of this high prevalence of OBI in Morocco need to be considered in laboratory diagnosis of HBV infection in HIV infected patients and the PCR seems to be inevitable for a better diagnosis and therapy.